Effect of molasses based multi-nutrients and chromium supplementation on milk quality and serum biochemistry of mid and late lactating Murrah buffaloes (Bubalus bubalis) - PATIL, A K; VERMA, A K; SINGH, PUTAN; MUNDE, V K; DAS, ASIT (The Indian Journal of Animal Sciences, 2021)
Lactating Murrah buffaloes (28) were divided into 4 groups of 7 each to study the effect of supplement molasses based multi-nutrient containing chromium picolinate on milk quality and serum biochemistry. Basal diet comprising wheat straw, maize green and concentrate mixture were fed to all the groups. In addition to basal diet, the animals were fed 250 g molasses based multi-nutrient supplement (MMS-1), 5 mg Cr-picolinate and MMS-2 (MMS + 5 mg Cr picolinate) in groups T2, T3 and T4, respectively. Daily milk yield and monthly milk composition were recorded. Blood samples were collected from the jugular vein on days 0, 90 and 180 of experimental feeding for the estimation of serum metabolite profile, concentrations of insulin, non-esterified fatty acid (NEFA), beta-hydroxybutyric acid (BHBA), T3, T4, IGF-1, cortisol, estradiol, progesterone and Cr levels. Results have revealed that the serum Cr concentration increased in Cr supplemented groups; however, the milk Cr concentration was comparable among all the groups. Hematological parameters were statistically comparable among 4 groups except that RBC concentration was higher in group T2. Fat corrected milk (FCM), solid corrected milk (SCM), energy corrected milk (ECM) yields and milk energy contents were significantly higher in MMS supplement groups. Supplementation of MMS and Cr-picolinate had no effect on serum estradiol, NEFA, BHBA, T3, T4, cortisol and IGF-1, however, the concentration of progesterone was significantly lower in all supplemented groups. From the results, it may be deduced that the supplementation of Cr has no adverse effect on FCM yield, however, supplementation of MMS improved FCM yield by 28%. No synergistic effect of supplementation of Cr and MMS on milk composition (fat, protein, SNF, TS and lactose) was observed in lactating Murrah buffaloes.